2018
DOI: 10.1007/s10384-018-0612-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of side effects of topical atropine sulfate and cyclopentolate hydrochloride for cycloplegia in Japanese children: a multicenter study

Abstract: Atropine has a side effect incidence rate 7 times higher than the incidence rate of cyclopentolate. Flush and fever are the most common side effects of atropine and drowsiness is the main side effect of cyclopentolate. These findings should be noted when examining cycloplegic refraction to manage amblyopia and strabismus in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 14 publications
1
32
1
Order By: Relevance
“…Shanker and Nigam [9] administered 1% atropine twice a day for 1 week with punctual occlusion to relax the accommodation of a patient with the spasm of near reflex. However, Wakayama et al [10] reported a higher incidence of adverse effect with 1% atropine compared to 0.5 and 0.25%. Hence, we decreased the concentration due to the prolonged use of atropine in our patient.…”
Section: Discussionmentioning
confidence: 97%
“…Shanker and Nigam [9] administered 1% atropine twice a day for 1 week with punctual occlusion to relax the accommodation of a patient with the spasm of near reflex. However, Wakayama et al [10] reported a higher incidence of adverse effect with 1% atropine compared to 0.5 and 0.25%. Hence, we decreased the concentration due to the prolonged use of atropine in our patient.…”
Section: Discussionmentioning
confidence: 97%
“…This phenomenon often develops into a high fever known as ‘atropine fever’ [ 8 , 9 ]. The frequency of ophthalmic atropine drop-induced fever in children has been reported at 1.3% (2/160) [ 7 ], 3.9% (32/811) [ 10 ], 4.0% (13/326) [ 11 ], and 72.7% (48/66) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Garg and Sinha [12] reported that in several children (6/66) in New Delhi, India, fever reached > 40 °C (no method of measurement was reported). Whereas the above reports [7, 8, 10–12] lacked detailed environmental descriptions, Magbagbeola [13] reported that in Ibadan, Nigeria, 58.5% (117/200) of children administered intramuscular injections of atropine as premedication for surgery had increased body temperature; the hospital ward had no air conditioning, an ambient temperature of 28.74 ± 0.13 °C, and a mean relative humidity of 71.59 ± 0.54%. That is to say, hot weather may be one of the risk factors for this type of hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…Atropine is the gold standard for evaluating cycloplegic refraction. 5,6 However, its long action, which results in prolonged blurred vision and a lengthy recovery time, has limited its application, particularly among elder children and adults. Besides atropine, the most commonly used cycloplegic agents are tropicamide and cyclopentolate.…”
Section: Introductionmentioning
confidence: 99%